HEGEMONI KEPALA DESA DALAM TRADISI SELAMATAN KAMPUNG DAN IDER BUMI DI REJOSARI KECAMATAN GLAGAH KABUPATEN BANYUWANGI - Dhalia Soetopo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
Ider salvation hometown and earth represents the culture of the village Rejosari in Banyuwangi. Every year the villagers held a series of cultural and it has become a tradition for them. Tradition salvation hometown and earth Ider conducted one week after Eid al-Adha. The process begins with doing Ider earth went around the village and ends with a meal with their families in the courtyard of the house. Ider village and the salvation of the earth has significance for the villagers Rejosari. Some of them are as repellent reinforcements and pagebluk. In addition there is also interpret it as a time to gather with relatives. In the implementation of salvation village tradition and Ider earth can not be separated from the committee system. The system may come from the community itself or come from rural management system. Both systems can not be separated from the influence of the head of the village. The village head has a strong role salvation implementation Ider village and the earth in the village Rejosari. Keywords : hegemony, tradition, salvation village, Ider earth